Determinación de las propiedades físicas, químicas y la relación C/N de tres tipos diferentes de abonos orgánicos en la Quinta Experimental la Argelia - Quituisaca Bure, Jhulissa Veronica (2023)
The research was carried out in the canton and province of Loja, Loja canton, Puzzara parish, Los Molinos part of the Quinta Experimental La Argelia. The importance of this work roots in evaluating the physical and chemical characteristics and the C/N relation of three different types of organic fertilizers. Organic fertilizers have great economic, social and environmental importance in recent years, so it is necessary to know the best quality organic fertilizer for its contribution in cultivated land that suffers from the loss of a large amount of nutrients. To carry out the research, a completely random experimental design (CRD) was established with three treatments and three repetitions. Each experimental unit constituted 3 m2. A parametric analysis of variance (ANOVA) was applied with 95% confidence. The results showed that the three treatments are within the ranges required for a quality fertilizer, however, the T3 humus was the best fertilizer in the experimental test, since, this not only meets the required parameters in terms of physical and chemical, it is also superior to compost and bocashi in all parameters except pH, electrical conductivity and C/N relation, so it is optimal to be applied to agricultural soils, for the improvement of their chemical degradation conditions. In addition, an optimal C/N relation of the raw materials was obtained prior to mixing for the production of organic fertilizers T1 33:1, T2 25:1 and T3 27:1, respectively, which implies a moderate availability of nitrogen and carbon in all treatments and was finalized with a correct C/N ratio in the three bocashi 9:1 treatments, compost 12:1 and humus 4:1. Keywords: C/N relation, carbon/nitrogen relation.